Enactivism and Ecological Psychology: The Role of Bodily Experience in Agency - Popova, Yanna B.; Rączaszek-Leonardi, Joanna (Frontiers in Psychology, 2020)
This paper considers some foundational concepts in ecological psychology and in enactivism., and traces their developments from their historical roots to current preoccupations. Important differences stem, we claim, from dissimilarities in how embodied experience has been understood by the ancestors, founders and followers of ecological psychology and enactivism, respectively. Rather than pointing to differences in domains of interest for the respective approaches, and restating possible divisions of labor between them in research in the cognitive and psychological sciences, we call for a deeper analysis of the role of embodiment in agency that we also undertake. Awareness of the differences that exist in the respective frameworks and their consequences, we argue, may lead to overcoming some current divisions of labor and responsibility, and contribute to a more comprehensive and complementary way of dealing with a broader range of theoretical and practical concerns. While providing some examples of domains, such as social cognition and art reception, in which we can observe the relative usefulness and potential integration of the theoretical and methodological resources from the two approaches, we demonstrate that such deeper synergy is not only possible but also beginning to emerge. Such complementarity, as we envisage, conceives of ecological psychology that allows felt experience as a crucial dynamical element in the explanations and models that it produces, and of an enactive approach that takes into consideration the ubiquitous presence of rich directly perceived relations among variables arising from enactments in the social and physical world.